2022
DOI: 10.1021/acs.joc.2c00627
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of γ-Pyrones and N-Methyl-4-pyridones via the Au Nanoparticle-Catalyzed Cyclization of Skipped Diynones in the Presence of Water or Aqueous Methylamine

Abstract: Supported Au nanoparticles on TiO2 catalyze the hydration/6-endo cyclization of skipped diynones to γ-pyrones in aqueous dioxane, via triple bond activation. The isomeric 3­(2H)-furanones which could be formed through a competing and often prevailing 5-exo cyclization pathway using homogeneous ionic Au­(I) catalysts were not seen. The reaction does not proceed via the initial 1,3-transposition of the skipped diynones to their corresponding conjugated 1,3-diynone isomers. If aqueous methylamine is added, N-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Increasing the AW/MD from 0 to 1.5 raised polysaccharide content of feedstock mixture linearly and decreased the pH of feedstock mixture exponentially, that is, from pH 7.1 to 5.5 (see Figure ). The decreasing feedstock pH to 5.5 enhanced the conversion of polysaccharides into biocrude oil due to higher selectivity for the formation of pyrones, cyclic C 5 -ketones, and furandiones (see Table S19) via dehydration of polysaccharides’ monomers into 5-HMF and furfural followed by isomerization, , Piancatelli rearrangement, and cyclization, respectively. In addition, a feedstock pH of around 5.5 has been reported to induce 5-HMF rehydration and lignin acidolysis with formic acid and formaldehyde as the side products, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the AW/MD from 0 to 1.5 raised polysaccharide content of feedstock mixture linearly and decreased the pH of feedstock mixture exponentially, that is, from pH 7.1 to 5.5 (see Figure ). The decreasing feedstock pH to 5.5 enhanced the conversion of polysaccharides into biocrude oil due to higher selectivity for the formation of pyrones, cyclic C 5 -ketones, and furandiones (see Table S19) via dehydration of polysaccharides’ monomers into 5-HMF and furfural followed by isomerization, , Piancatelli rearrangement, and cyclization, respectively. In addition, a feedstock pH of around 5.5 has been reported to induce 5-HMF rehydration and lignin acidolysis with formic acid and formaldehyde as the side products, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for this discrepancy is that 1a rearranges or degrades on the gold surface. Indeed, while our work was in progress, it was reported that related diynones rearrange to γ-pyrones in the presence of gold nanoparticles supported on titania (Au/TiO 2 ) in solution, initiated by the aurophilicity of the triple bonds . We, therefore, synthesized the corresponding γ-pyrone derivative 4 by acid-catalyzed rearrangement of 1a following a literature route: compound 4 would be the expected product of the Au-catalyzed rearrangement of 1a .…”
Section: Resultsmentioning
confidence: 99%
“…The chemistry of these heterocycles is actively developed not only for the design of biologically important compounds [ 7 , 8 , 9 ], but also for effective preparation in the industry [ 1 , 2 , 3 , 10 , 11 , 12 , 13 , 14 , 15 ]. At the same time, there is a need to search for new multifarious pyridone building blocks [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and convenient synthetic tools for the construction of polycyclic pyridones [ 1 , 2 , 3 , 15 ], including CH functionalization [ 26 ].…”
Section: Introductionmentioning
confidence: 99%